Vagal-immune interactions involved in cholinergic anti-inflammatory pathway - Zila, I; Mokra, D; Kopincova, J; Kolomaznik, M; Javorka, M; Calkovska, A (Physiological research, 2017)
Inflammation and other immune responses are involved in the variety of diseases and disorders. The acute response to endotoxemia includes activation of innate immune mechanisms as well as changes in autonomic nervous activity. The autonomic nervous system and the inflammatory response are intimately linked and sympathetic and vagal nerves are thought to have anti-inflammation functions. The basic functional circuit between vagus nerve and inflammatory response was identified and the neuroimmunomodulation loop was called cholinergic anti-inflammatory pathway. Unique function of vagus nerve in the anti-inflammatory reflex arc was found in many experimental and pre-clinical studies. They brought evidence on the cholinergic signaling interacting with systemic and local inflammation, particularly suppressing immune cells function. Pharmacological/electrical modulation of vagal activity suppressed TNF-alpha and other proinflammatory cytokines production and had beneficial therapeutic effects. Many questions related to mapping, linking and targeting of vagal-immune interactions have been elucidated and brought understanding of its basic physiology and provided the initial support for development of Tracey´s inflammatory reflex. This review summarizes and critically assesses the current knowledge defining cholinergic anti-inflammatory pathway with main focus on studies employing an experimental approach and emphasizes the potential of modulation of vagally-mediated anti-inflammatory pathway in the treatment strategies.
Keywords: Cholinergic Agents; neurony cholinergní; Animals; antiflogistika; Inflammation; Signal Transduction; Vagus Nerve; lidé; zánět; nervus vagus; zvířata; neuroimunomodulace; Cholinergic Neurons; Anti-Inflammatory Agents; signální transdukce; Neuroimmunomodulation; cholinergní látky; Humans